Silk / GO composite membrane, preparation method thereof and application of silk / GO composite membrane in salinity gradient power generation device

By using silk/GO composite membrane as the separator for the salt-difference power generation device, the problem of limited ion transmission capacity in the prior art is solved, the power generation efficiency is significantly improved, and the self-power supply capacity of the portable rescue lamp is realized.

CN119735837APending Publication Date: 2025-04-01HEILONGJIANG UNIV
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411900824.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The separator used in existing salt-difference power generation devices has limited ion transmission capacity, resulting in low salt-difference power generation efficiency.

Method used

Silk/GO composite film is used as the separator film, and the interface connection and ion transport behavior between nanoparticles are improved by compositeing silk with graphene oxide and preparing with polycarbonate film as the substrate.

Benefits of technology

It significantly improves the power generation efficiency of the salt-difference power generation device and effectively solves the problem of short working hours of offshore emergency rescue equipment and inability to supply power by itself.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735837A_ABST
    Figure CN119735837A_ABST
Patent Text Reader

Abstract

The invention discloses a silk / GO composite film, a preparation method thereof and application of the silk / GO composite film in a salinity gradient power generation device, and belongs to the technical field of functional films and preparation of the functional films. According to the invention, the problem of low salinity gradient power generation efficiency caused by limited ion transmission capability of the existing separation membrane for salinity gradient power generation is solved. Silk and graphene oxide are used as raw materials, and a polycarbonate film is used as a substrate to prepare the silk / GO composite film. According to the composite membrane, silk and graphene oxide are compounded to form a stable frame structure, so that the interface connection among nanoparticles is greatly improved, and the ion transmission behavior is also remarkably improved, so that the salinity gradient power generation device based on the seawater salinity gradient has relatively high power generation efficiency. The light source is coupled with a marine emergency rescue system, the advantages of energy of the seawater environment and the like are effectively utilized, and the prepared portable rescue lamp is expected to solve the key scientific and technical problems that marine rescue equipment is short in working time and cannot be self-powered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a silk / GO composite membrane and a preparation method thereof and application in a salt difference power generation device, belonging to the technical field of functional films and preparation methods thereof. Background Art

[0002] Marine rescue lights are an effective way to call for help in an emergency. However, existing portable marine emergency rescue lights ("SOS") generally face problems such as short working time and the need for external power supply, which limits the large-scale promotion and use of these devices. Designing and manufacturing a self-powered portable marine emergency rescue light has become an urgent social need.

[0003] Salt difference energy is a new type of widely available clean energy. Its principle is to use the concentration difference between two solutions to convert salt difference energy into electrical energy through reverse electrodialysis technology to power electronic devices. There are a large number of high-concentration solutions in seawater, which provide a continuous source of raw materials for salt difference power generation. Combining the salt difference power generation system with the marine emergency rescue system to prepare a portable rescue light is expected to solve the key technical problems of short working hours and inability to self-power marine rescue equipment. However, due to the limitations of the ion transmission capacity of the separator membrane used in the existing salt difference power generation device, the existing salt difference power generation still has the problem of low efficiency. Summary of the invention

[0004] Aiming at the problem that the existing separator membrane for salt difference power generation has limited ion transmission capacity, resulting in low salt difference power generation efficiency, the present invention provides a silk / GO composite membrane and a preparation method thereof and application in a salt difference power generation device.

[0005] The technical solution of the present invention:

[0006] One of the objects of the present invention is to provide a method for preparing a silk / GO composite membrane, which comprises:

[0007] (1) adding silk cocoons to a boiling sodium bicarbonate solution and continuously boiling for 2 times, each time for 10 to 60 minutes, rinsing the obtained product, spreading it on a clean aluminum foil and drying it in a fume hood to obtain silk;

[0008] (2) adding silk to a hexafluoroisopropanol aqueous solution, stirring until completely dissolved, heating and sealing, and then standing at 60°C for storage, then opening the seal and drying in a fume hood to allow the hexafluoroisopropanol to completely evaporate, transferring to pure water, stirring thoroughly, filtering to remove insoluble matter, subjecting the obtained solution to ultrasonic and centrifugal treatment, taking the supernatant as the silk solution, and sealing and storing at low temperature;

[0009] (3) dissolving the monolayer GO powder in water, crushing it with a cell crusher to obtain a uniform dispersion, and adjusting the pH with ammonia water to obtain a GO solution;

[0010] (4) mixing the silk solution and the GO solution and then subjecting the mixture to ultrasonic treatment to obtain a mixed solution;

[0011] (5) Using a polycarbonate membrane as a substrate, the mixed solution is subjected to vacuum filtration treatment, and the obtained membrane layer is placed in an oven for heating treatment to obtain a silk / GO composite membrane.

[0012] It is further defined that the concentration of the sodium bicarbonate solution in (1) is 0.1 to 5%.

[0013] It is further defined that the concentration of the sodium bicarbonate solution in (1) is 0.5%.

[0014] It is further defined that the mass volume ratio of the silkworm cocoon and the sodium bicarbonate solution in (1) is (0.1-5) g:200 mL.

[0015] It is further defined that the mass volume ratio of the silkworm cocoon and the sodium bicarbonate solution in (1) is 0.5 g:200 mL.

[0016] It is further defined that the boiling time in (1) is 30 minutes each time.

[0017] It is further defined that the rinsing in (1) is washing with cold water and water at room temperature in sequence and squeezing dry, and the above operation is repeated three times.

[0018] It is further defined that the concentration of the hexafluoroisopropanol aqueous solution in (2) is 0.1 to 5%.

[0019] It is further defined that the concentration of the hexafluoroisopropanol aqueous solution in (2) is 3.3%.

[0020] It is further defined that the heating and sealing temperature in (2) is 40 to 80° C. and the static storage time is 8 to 48 hours.

[0021] It is further defined that the heating sealing temperature in (2) is 60°C and the static storage time is 24h.

[0022] It is further defined that the ultrasonic treatment power in (2) is 10 to 50 kHz and the time is 30 to 180 min.

[0023] It is further defined that the ultrasonic treatment power in (2) is 20 kHz and the time is 60 min.

[0024] It is further defined that the centrifugal treatment speed in (2) is 5000 to 20000 rpm and the time is 10 to 60 min.

[0025] It is further defined that the centrifugal treatment speed in (2) is 10000 rpm and the time is 20 min.

[0026] It is further defined that (2) the low temperature storage temperature is 4°C.

[0027] It is further defined that the concentration of the dispersion in (3) is 1 to 100 mg / mL, and the pH is adjusted to 9 to 13 using aqueous ammonia.

[0028] It is further defined that the concentration of the dispersion in (3) is 9 mg / mL.

[0029] Further, in (3), the pH is adjusted to 10 using aqueous ammonia.

[0030] It is further defined that the volume ratio of the silk solution to the GO solution in (4) is 1:1 to 1:20.

[0031] It is further defined that the volume ratio of the silk solution to the GO solution in (4) is 1:5.

[0032] It is further defined that the ultrasonic treatment time in (4) is 5 to 30 minutes.

[0033] It is further defined that the ultrasonic treatment time in (4) is 10 min.

[0034] It is further defined that the filtration treatment time in (4) is 8 to 48 hours.

[0035] It is further specified that the filtration treatment time in (4) is 24 hours.

[0036] It is further defined that the heating treatment temperature in (4) is 50 to 90° C. and the time is 8 to 48 hours.

[0037] It is further defined that the heating treatment temperature in (4) is 80°C and the time is 24 hours.

[0038] The second object of the present invention is to provide a silk / GO composite membrane prepared by the above method.

[0039] It is further defined that the thickness of the silk / GO composite membrane is 20 to 100 μm.

[0040] The third object of the present invention is to provide an application of the silk / GO composite membrane, specifically for the preparation of a salt difference discharge device.

[0041] The fourth object of the present invention is to provide a salt difference power generation device, specifically 1 the device includes a container and a salt solution filled in the container, the container is separated into a low-concentration salt solution tank and a high-concentration salt solution tank by the above-mentioned silk / GO composite membrane, the low-concentration salt solution tank is filled with a salt solution with a concentration of 0.001 to 0.1 mol / L, and the high-concentration salt solution tank is filled with seawater.

[0042] It is further defined that the low concentration salt solution tank contains a salt solution with a concentration of 0.05 mol / L.

[0043] Beneficial effects:

[0044] The present invention uses silk and graphene oxide as raw materials and polycarbonate film as substrate to prepare a silk / GO composite membrane, which is applied to a salt difference power generation system and converts chemical energy into electrical energy by using the concentration difference of the electrolyte. Compared with the prior art, the present invention has the following advantages:

[0045] (1) The present invention combines silk with graphene oxide to form a stable framework structure, which not only greatly improves the interface connection between nanoparticles, but also significantly improves the ion transmission behavior, so that the salt difference power generation device based on the seawater salt concentration gradient has a higher power generation efficiency.

[0046] (2) The present invention couples the prepared silk / GO composite membrane with the marine emergency rescue system and applies it to a salt difference power generation device based on the seawater salt concentration gradient, effectively utilizing the advantages of the seawater environment's own energy and other advantages to prepare a portable rescue light that is expected to solve the key scientific and technological problems of the short working time and inability of self-power supply of marine rescue equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 This is a physical picture of the silk / GO composite membrane prepared in Example 1;

[0048] Figure 2 This is a SEM photo of the silk / GO composite membrane prepared in Example 1;

[0049] Figure 3 is a schematic diagram of a power generation device based on seawater salt concentration gradient;

[0050] Figure 4 The relationship between the current density and the external resistance of the power generation device based on the seawater salt concentration gradient prepared in Example 1;

[0051] Figure 5 The relationship between the power generation power and the external resistance of the power generation device based on the seawater salt concentration gradient prepared in Example 1;

[0052] Figure 6 The relationship between the current density and the external resistance of the power generation device based on the seawater salt concentration gradient prepared in Example 2;

[0053] Figure 7 The relationship between the power generation power and the external resistance of the power generation device based on the seawater salt concentration gradient prepared in Example 2;

[0054] Figure 8The relationship between the current density and the external resistance of the power generation device based on the seawater salt concentration gradient prepared in Example 3;

[0055] Fig. 9 This is a relationship diagram between the power generation power and external resistance of the power generation device based on seawater salt concentration gradient prepared in Example 3;

[0056] Fig.10 This is a comparison chart of ion flux between the silk / GO composite membrane and the polycarbonate membrane prepared in Example 1;

[0057] Fig.11 This is a comparison chart of the ion selectivity of the silk / GO composite membrane and the polycarbonate membrane prepared in Example 1. DETAILED DESCRIPTION

[0058] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0059] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0060] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0061] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art, and the purity of the solid and liquid reagents used is analytically pure.

[0062] Example 1

[0063] The method for preparing the silk / GO composite membrane in this embodiment comprises the following steps:

[0064] S1. Prepare 200 ml of sodium bicarbonate solution (concentration 1%) and boil;

[0065] S2. When the sodium bicarbonate solution starts to boil, add 1 g of silkworm cocoons and continue boiling for 2 times, each time for 30 minutes to obtain silk;

[0066] S3. The silk was washed with cold water, room temperature water and squeezed to remove excess water and sodium bicarbonate solution; and the above washing operation was repeated three times;

[0067] S4. After rinsing, spread the silk on clean aluminum foil and dry it in a fume hood overnight;

[0068] S5. The above product was put into a 3.3% hexafluoroisopropanol aqueous solution, stirred thoroughly until completely dissolved, heated and sealed at 50°C, and stored at 60°C for 48h;

[0069] S6. Then open the package and dry and evaporate in a fume hood to completely evaporate the hexafluoroisopropanol solution, then transfer it to pure water, stir it thoroughly, and filter out the insoluble matter;

[0070] S7. The solution was subjected to ultrasonic treatment (power 20 kHz, duration 60 min), and centrifuged (speed 10000 rpm, time 20 min) to separate the solid and liquid, and the supernatant was sealed in a solvent bottle and stored in a refrigerator at 4°C for later use;

[0071] S8. A monolayer GO powder (purchased from J&K, with a diameter of 0.5-5 μm and a thickness of 0.8-1.2 nm) was dissolved in water and crushed by a cell crusher to obtain a uniform solution with good dispersion and a concentration of 10 mg / ml;

[0072] S9. Add 0.01 mol / L ammonia water to the above homogeneous solution and adjust the pH to 10;

[0073] S10. The silk solution obtained in S7 and the GO solution obtained in S9 were mixed (volume ratio of 1:5) and ultrasonically treated for 10 min;

[0074] S11. Using a polycarbonate membrane as a substrate, the obtained mixed solution is subjected to vacuum filtration for 12 hours to obtain a composite membrane;

[0075] S12. The composite membrane was placed in a 60°C oven for 24 h to enhance the membrane strength and toughness, and a silk / GO composite membrane with a thickness of 20 μm was obtained. Figure 1 shown.

[0076] The cross-sectional morphology of the obtained silk / GO composite membrane was characterized. Figure 2 As shown by Figure 2 It can be seen that the composite membrane has a layered structure, which is dense and uniform.

[0077] The conductive current and potential of the obtained silk / GO composite membrane and GO membrane were characterized. The current was used to characterize the ion flux of the silk / GO composite membrane, and the potential was used to characterize the ion selectivity of the silk / GO composite membrane. The specific test method is: the IV curves of the two membrane materials are tested separately using an electrochemical test cell. The solutions on both sides of the membrane are potassium chloride solutions of equal concentration, with a concentration of 0.01 mol / L. The IV curve data of the two membrane materials are obtained using a picoammeter to calculate the transmembrane current; GO / SNF and GO are configured into six pH solutions of pH = 2, 4, 6, 8, 10, and 12, with a concentration of 0.001 / mg / ml, and then diluted 1000 times, and the zeta potential is obtained using a zeta potential meter. The test results are as follows: Fig.10 and Fig.11 As shown in the figure, 2D membrane represents GO membrane and NF-2D membrane represents silk / GO composite membrane. Fig.10 It can be seen that the current of the functionalized composite membrane is significantly improved, indicating that the ion transmembrane current is enhanced and the ion selective permeability is improved; analysis Fig.11 It can be seen that the surface potential of the functionalized composite membrane nanosheets is improved, which firstly proves the success of functionalization and secondly proves that the surface of the functionalized nanosheets has more negative charges, which is beneficial to cation selectivity.

[0078] like Figure 3 As shown, a salt difference power generation device is prepared using the silk / GO composite membrane prepared in this embodiment as a partition, wherein the reaction electrode is a sheet-like silver / silver chloride electrode, the solution filled in the low-concentration salt solution tank is a 0.01 mol / L sodium chloride solution, and the solution filled in the high-concentration solution tank is a 0.05 mol / L sodium chloride solution.

[0079] The relationship between the current density and power generation of the above-mentioned salt difference power generation device and the external resistance is characterized, and the results are as follows: Figure 4 and Figure 5 As shown by Figure 4 and Figure 5 It can be seen that when the external resistance is 100000Ω, the output power can reach 33W / m 2 .

[0080] Example 2

[0081] The difference between this embodiment and embodiment 1 is that the silk cocoon in S2 is 3 g, the concentration of GO solution in S8 is 50 mg / ml, and the remaining process steps and parameter settings are the same as those in embodiment 1, and a silk / GO composite membrane with a thickness of 50 μm is obtained.

[0082] A salt difference power generation device was prepared using the silk / GO composite membrane prepared in this embodiment as a partition, wherein the reaction electrode was a sheet silver / silver chloride electrode, the solution filled in the low concentration salt solution tank was a 0.01 mol / L sodium chloride solution, and the solution filled in the high concentration solution tank was artificial seawater (sodium chloride solution with a concentration of 0.5 mol / L).

[0083] The relationship between the current density and power generation of the above-mentioned salt difference power generation device and the external resistance is characterized, and the results are as follows: Figure 6 and Figure 7 As shown by Figure 6 and Figure 7 It can be seen that when the external resistance is 20000Ω, the output power can reach 545W / m 2 .

[0084] Example 3

[0085] The difference between this embodiment and embodiment 1 is that the silk cocoon in S2 is 5 g, the concentration of GO solution in S8 is 80 mg / ml, and the remaining process steps and parameter settings are the same as those in embodiment 1, and a silk / GO composite membrane with a thickness of 100 μm is obtained.

[0086] A salt difference power generation device was prepared using the silk / GO composite membrane prepared in this example as a partition, wherein the reaction electrode was a sheet-like silver / silver chloride electrode, the solution filled in the low-concentration salt solution tank was a 0.01 mol / L sodium chloride solution, and the solution filled in the high-concentration solution tank was a 5 mol / L sodium chloride solution).

[0087] The relationship between the current density and power generation of the above-mentioned salt difference power generation device and the external resistance is characterized, and the results are as follows: Figure 8 and Fig. 9 As shown by Figure 8 and Fig. 9 It can be seen that when the external resistance is 5000Ω, the output power can reach 4500W / m 2 .

[0088] Although the present invention has been disclosed as above in the preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for preparing a silk / GO composite membrane, characterized in that: include: (1) adding silk cocoons to a boiling sodium bicarbonate solution and continuously boiling for 2 times, each time for 10 to 60 minutes, rinsing the obtained product, spreading it on a clean aluminum foil and drying it in a fume hood to obtain silk; (2) adding silk to a hexafluoroisopropanol aqueous solution, stirring until completely dissolved, heating and sealing, and standing at 60° C., then opening the seal and drying in a fume hood to allow the hexafluoroisopropanol to completely evaporate, transferring to pure water, stirring thoroughly, filtering to remove insoluble matter, subjecting the obtained solution to ultrasonic and centrifugal treatment, taking the supernatant as the silk solution, and sealing and storing at low temperature; (3) dissolving the monolayer GO powder in water, crushing it with a cell crusher to obtain a uniform dispersion, and adjusting the pH with ammonia water to obtain a GO solution; (4) mixing the silk solution and the GO solution and then subjecting the mixture to ultrasonic treatment to obtain a mixed solution; (5) Using a polycarbonate membrane as a substrate, the mixed solution is subjected to vacuum filtration treatment, and the obtained membrane layer is placed in an oven for heating treatment to obtain a silk / GO composite membrane.

2. The preparation method according to claim 1, characterized in that: (1) The concentration of the sodium bicarbonate solution is 0.1-5%; the mass volume ratio of the silkworm cocoon and the sodium bicarbonate solution is (0.1-5) g: 200 mL.

3. The preparation method according to claim 1, characterized in that: (2) The concentration of the hexafluoroisopropanol aqueous solution is 0.1-5%; the heating and sealing temperature is 40-80° C., and the static storage time is 8-48 hours.

4. The preparation method according to claim 1, characterized in that: (2) The ultrasonic treatment power is 10-50 kHz, and the time is 30-180 min; the centrifugal treatment speed is 5000-20000 rpm, and the time is 10-60 min.

5. The preparation method according to claim 1, characterized in that: The concentration of the dispersion in (3) is 1 to 100 mg / ml, and the pH is adjusted to 9 to 13 using aqueous ammonia.

6. The preparation method according to claim 1, characterized in that: (4) The volume ratio of the silk solution to the GO solution is 1:1 to 1:

20.

7. The preparation method according to claim 1, characterized in that: (4) The filtration treatment time is 8 to 48 hours; the heating treatment temperature is 50 to 90°C and the time is 8 to 48 hours.

8. A silk / GO composite membrane prepared by the method according to any one of claims 1 to 7, characterized in that: The thickness is 20 to 100 μm.

9. An application of the silk / GO composite membrane according to claim 8, characterized in that: Used for the preparation of salt difference discharge device.

10. A salt difference power generation device, characterized in that: The device comprises a container and a salt solution filled in the container, wherein the container is divided into a low-concentration salt solution tank and a high-concentration salt solution tank by the silk / GO composite membrane according to claim 8, the low-concentration salt solution tank contains a salt solution with a concentration of 0.001 to 0.1 mol / L, and the high-concentration salt solution tank contains seawater.

Citation Information

Patent Citations

  • Graphene oxide and silk fibroin composite membrane and preparation method thereof

    CN102940907A

  • Graphene modified silk fiber preparing method

    CN105926075A

  • Asymmetric nanopore composite film and preparation method and application thereof

    CN109847594A

  • Preparation method of reduced graphene oxide silk fibroin composite membrane

    CN111939318A

  • Preparation method of extracellular polymeric substance intercalation MXene two-dimensional membrane for salinity gradient energy power generation

    CN116655965A